Chemical characterization and antioxidant capacity of ‘Cambui’ (Myrciaria tenella) products - Rybka, Ana Cecília Poloni; Marques, Aline Camarão Telles Biasoto; Araújo, Ana Júlia; Nassur, Rita de Cassia Mirela Resende (Comunicata Scientiae, 2019)
Very little information is found about the ‘Cambui’ products and the fruit is almost unexplored by the Brazilian agriculture or extractive activities. The present study aimed to characterize the physicochemical composition and antioxidant capacity of the juice, jam and fermented beverage obtained from ‘Cambuí’ fruits aiming to add value to the fruit and generate alternatives to Brazilian extractive population. These products were elaborated in small scale of production. The ‘Cambuí’ juice was prepared using the method of steam distillation and the jam was obtained from the residue of the juice with addition of sugar and citric acid. The ‘Cambuí’ fermented beverage was elaborated using procedures of winemaking. For the evaluation of the products quality, chemical analysis and evaluation of the antioxidant capacity were performed. All products presented high concentrations of the studied variables, when comparing to grape wines, fruit jams and grape juices. The ‘Cambui’ products can be considered sources of antocyanins and other phenolic compounds, with high antioxidant potential. The use of ‘Cambui’ has potential for the development of juice, jam and fermented beverage, and these products can be an alternative to add value to fruit and generate income for populations that work with which income depend on extractive activities.